Cranial nerve palsies in spontaneous carotid artery dissection. Issue 11 (November 1993) - Sturzenegger, M; Huber, P
Abstract : Two patients had isolated unilateral cranial nerve palsies due to spontaneous internal carotid artery (ICA) dissection without ischaemic cerebral involvement. One had acute glossopharyngeal and vagal, the other isolated hypoglossal nerve palsy. Reviewing all reported cases of angiographically confirmed ICA dissection in the literature, 36 additional cases with unequivocal ipsilateral cranial nerve palsies were analysed. While an isolated palsy of the IXth and Xth has not been reported previously, palsies of the XIIth nerve or the IXth to XIIth nerves were most frequently found. In these patients, lower cranial nerve palsies are probably the result of compression by an enlarging ICA due to mural haematoma. Symptoms and signs indicative of carotid dissection were concurrently present only in some reported cases. This raises the question of unrecognised carotid dissection as a cause of isolated cranial nerve palsies. When the dissection occurs in the subadventitial layer without relevant narrowing of the arterial lumen and when an aneurysm is thrombosed, angiography does not reliably yield the diagnosis. Therefore, carotid dissection might have been underestimated as a cause of isolated lower cranial nerve palsies before the advent of MRI. MRI demonstrates directly the extension of the wall haematoma in the axial and longitudinal planes. Some arteriopathies such as fibromuscular dysplasia and tortuosity make a vessel predisposed to dissection.